Structure of the macrobenthonic of Paca Lagoon, Junín - Huamán, Pedro (2002)
A characterization was made of structural aspects of macrobenthos in Paca lagoon, which is located at 3364 meters, to 11º 45´ S and 75º 30´ W on the department of Junín, Peru. At the same time, the physical and chemical factors of water and sediment were analyzed. The samples were collected in 8 stations at the littoral region (5) and the Pelagic region (3) during the year of 2000. The samples were taken from each station from the bottom in order to analyze the physical, chemical and biological parameters from macrobenthic community; the samples were found to contain some sediment and water. The results were tested to find out the interaction of the factors with the biological variables. The macrobenthos diversity is poor and shows values smaller than 1,5 and number of species is smaller than 11. The abundance ranges between 16 to 176 ind/0,04 m2 . Tubifex tubifex and Chironomus sp were the species more resistant to the high organic matter values (35,22–38,28%) and low values of free oxigen (1–2 ppm), which points out to eutrophication biological markers.